What drives regional unemployment rate disparities in European regions? - Vicente Rios Iba\~nez (European Regional Science Association (ERSA), 2014)
This paper investigates the evolution of the geographical distribution of unemployment rates in a sample of 258 NUTS-2 European regions between 2000 and 2011. In particular, I explore the role played by market equilibrium, disequilibrium and institutional factors shaping regional unemployment disparities. To that end, the present analysis uses recently developed spatial panel econometric techniques that integrate spatial and temporal dynamics. Important methodological issues such as region-speci_x000C_c and time-speci_x000C_c _x000C_xed e_x000B_ects, spatial estimation methods, speci_x000C_cation and the selection of the spatial matrix are addressed. In conjunction with spatio-temporal panel data regression model estimates, stochastic kernels are used to analyze the e_x000B_ect of the various factors in the shape of the whole distribution of unemployment rate. Empirical results suggest that regional unemployment rate di_x000B_erences have decreased and that such regional convergence process has been driven by regional market equilibrium factors.
Keywords: 330; Unemployment; Spatial Dynamic Lag; Stochastic Kernels